Population size estimation of the exotic crayfish Procambarus clarkii (Girard) (Crustacea, Decapoda, Cambaridae) in the Alfredo Volpi City Park, São Paulo, Brazil - Silva,Humberto Leandro Melo da (2005)
The size of a well established adult population of the exotic cambarid crayfish Procambarus clarkii (Girard, 1852) from a artificial pond at the Alfredo Volpi City Park, in the city of São Paulo, Brazil, is estimated in four different occasions between 1999 and 2001 by means of a mark-and-recapture technique and Schumacher and Eschmeyer's method for population size determination. Adults were marked by placing small elastic rings at the base of both eyestalks. Population size varied from approximately 269 and 273 adults (the latter corrected by Tanaka's model) in the summer in 2000 and 2001, and between 640 and 468 adults during the winter season of 1999 and 2000, respectively.